Patterns and profiles of drug resistance-conferring mutations in Mycobacterium tuberculosis genotypes isolated from tuberculosis-suspected attendees of spiritual holy water sites in Northwest Ethiopia - Reta, Melese Abate; Maningi, Nontuthuko Excellent; Fourie, P. Bernard (Frontiers in Public Health, 2024)
Purpose: This study examined the patterns and frequency of mutations conferring resistance to firstline (rifampicin (RIF) and isoniazid (INH)), and second-line (fluoroquinolones (FLQs) and injectable drugs (SLIDs)) in drug-resistant Mycobacterium tuberculosis (MTB) isolated from culture-positive pulmonary tuberculosis (PTB) symptomatic attendees of spiritual holy water sites (HWSs) in Ethiopia. Patients and Methods: A cross-sectional study was carried out from June 2019 to March 2020. A total of 122 culture-positive MTB isolates from PTB suspected attendees of HWSs in the Amhara region were evaluated for their drug resistance profiles, and characterized gene mutations conferring resistance to RIF, INH, FLQs, and SLIDs using GenoType ® MTBDRplus VER2.0 and GenoType ® MTBDRsl VER2.0. Drug-resistant MTB isolates were Spoligotyped following the manufacturer's protocol.Results: Gene mutations responsible for resistance to RIF, INH, and FLQs were identified in 15/122 (12.3%), 20/122 (16.4%), and 5/20 (25%) of MTB isolates, respectively. In RIF-resistant, rpoB/Ser531Lue (n=12, 80%) was most frequent followed by His526Tyr (6.7%). Amongst INHresistant isolates, katG/Ser315Thr1 (n=19, 95%) was most frequent. Of 15 MDR-TB, the majority (n=12,80%) isolates had mutations at both rpoB/Ser531Leu and katG/Ser315Thr1. All 5 FLQresistant isolates had mutations at rpoB/Ser531Lue, katG/Ser315Thr1, and gyrA/Asp94Ala genes.Of 20 Spoligotyped drug-resistant MTB isolates, the majority (n=11, 55%) and 6 (30%) were SIT149/T3-ETH and SIT21/CAS1-Kili sublineages, respectively; and they were any INH-resistant (mono-hetero/multi-). Of 15 RIF-resistant (RR/MDR-TB) isolates, 7 were SIT149/T3-ETH, while 6 were SIT21/CAS1-Kili sublineages. FLQ resistance was detected in four SIT21/CAS1-Kili lineages.In the current study, the most common gene mutations responsible for resistance to RIF, INH, and FLQs were identified. SIT149/T3-ETH and SIT21/CAS1-Kili constitute the majority of DR-TB isolates. To further understand the complete spectrum of mutations and related genotypes, a sequencing technology is warranted.